Use of Standardised Patients to Assess Antibiotic Dispensing for Tuberculosis by Pharmacies in Urban India : A Cross-Sectional Study - Satyanarayana, Srinath; Kwan, Ada; Daniels, Benjamin; Subbaraman, Ramnath; McDowell, Andrew; Bergkvist, Sofi; Das, Ranendra K.; Das, Veena; Das, Jishnu; Pai, Madhukar (Elsevier, 2019)
India's total antibiotic use is the highest of any country. Patients often receive prescription-only drugs directly from pharmacies. Here we aimed to assess the medical advice and drug dispensing practices of pharmacies for standardized patients with presumed and confirmed tuberculosis in India. In this cross-sectional study in the three Indian cities Delhi, Mumbai, and Patna, we developed two standardized patient cases: first, a patient presenting with 2–3 weeks of pulmonary tuberculosis symptoms (Case 1); and second, a patient with microbiologically confirmed pulmonary tuberculosis (Case 2).